Management of transition dipoles in organic hole-transporting materials under solar irradiation for perovskite solar cells - Ok, Song Ah; Jo, Bonghyun; Somasundaram, Sivaraman; Woo, Hwi Je; Lee, Dae Woon; Li, Zijia; Kim, Bong Gi; Kim, Jong H.; Song, Young Jae; Ahn, Tae Kyu; Park, Sanghyuk; Park, Hui Joon (Nature Communications, 2018)
In organic hole-transporting material (HTM)-based p−i−n planar perovskite solar cells, which have simple and low-temperature processibility feasible to flexible devices, the incident light has to pass through the HTM before reaching the perovskite layer. Therefore, photo-excited state of organic HTM could become important during the solar cell operation, but this feature has not usually been considered for the HTM design. Here, we prove that enhancing their property at their photo-excited states, especially their transition dipole moments, can be a methodology to develop high efficiency p−i−n perovskite solar cells. The organic HTMs are designed to have high transition dipole moments at the excited states and simultaneously to preserve those property during the solar cell operation by their extended lifetimes through the excited-state intramolecular proton transfer process, consequently reducing the charge recombination and improving extraction properties of devices. Their UV-filtering ability is also beneficial to enhance the photostability of devices.